Pemanfaatan Edukasi-net dalam Pencarian Sumber Belajar melalui Akses Internet - Suwarsito Suwarsito; Harjono Harjono (JUITA : Jurnal Informatika, 2010)
The service in the form of this training aimed at giving the training to teaching staff (the teacher) of SLTP in the Banyumas Regency about the utilisation of the computer as results of the IPTEKS development of taking the form of the internet to search some references of learning such as Edukasi-net. This training was carried out in the Multimedia Laboratory of – Informatic Technique Study Program – UMP by using the talk method, the demonstration, the interview (discussions), and the direct practice of internet access. As for intensive training time was carried out for 2 day by taking up time 16 hours from 08.00 to 16.00 each day with the number of participants 45 SLTP teachers in the Banyumas Regency. Based on the evaluation that was carried out, was received by results that 90% smooth participants in using edukasi-net to get some references, and 100% have from the number of participants had the e-mail address (the account e-mail). Participants were very enthusiastic in joining the training. From participants who joined the training, totalling 100% stated that the training that was carried out had the good and beneficial impression, so as very necessary to be followed up by the similar training activities with various contents of training material in the future especially the training in the computer field.